2016
DOI: 10.2967/jnumed.115.167932
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Imaging of the Atypical Chemokine Receptor 3 (ACKR3/CXCR7) in Human Cancer Xenografts

Abstract: The atypical chemokine receptor ACKR3 (formerly CXCR7), overexpressed in various cancers compared to normal tissues, plays a pivotal role in adhesion, angiogenesis, tumorigenesis, metastasis and tumor cell survival. ACKR3 modulates the tumor microenvironment and regulates tumor growth. The therapeutic potential of ACKR3 has also been demonstrated in various murine models of human cancer. Literature findings underscore the importance of ACKR3 in disease progression and suggest it as an important diagnostic make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…To our knowledge, currently there are no reported therapeutic mAbs against ACKR3 in preclinical or clinical development. One group reported an application of 89 Zr-11G8, a radiolabeled murine IgG1, for positron emission tomography studies in xenograft mice but without any therapeutic effects described (Behnam Azad et al, 2016). This contrasts with a relatively broad panel of mAbs targeting CXCR4, as summarized in Table 2.…”
Section: Targeting Cxcr4 and Ackr3 With Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, currently there are no reported therapeutic mAbs against ACKR3 in preclinical or clinical development. One group reported an application of 89 Zr-11G8, a radiolabeled murine IgG1, for positron emission tomography studies in xenograft mice but without any therapeutic effects described (Behnam Azad et al, 2016). This contrasts with a relatively broad panel of mAbs targeting CXCR4, as summarized in Table 2.…”
Section: Targeting Cxcr4 and Ackr3 With Antibodiesmentioning
confidence: 99%
“…mAbs targeting CXCR4 or ACKR3 were used as in vivo imaging tools. In this case, antibodies were radiolabeled with 89 Zr and could detect GPCR expression in xenograft tumors in mice using positron emission tomography (Azad et al, 2016;Behnam Azad et al, 2016). To our knowledge, no GPCRtargeting nanobodies have been used thus far for in vivo imaging.…”
Section: Single-domain Antibodies As Therapeutics and Tools In Gpcr Rmentioning
confidence: 99%
“…CXCL12 has been labeled using an iodine-125 label on tyrosine residues and also with Alexa Fluor 647 (Bleul et al, 1996;Oberlin et al, 1996;Hesselgesser et al, 1997Hesselgesser et al, , 1998Di Salvo et al, 2000). Radioiodination has also been introduced to CXCR4 and ACKR3 antibodies and peptides (Endres et al, 1996;Koglin et al, 2006;Han et al, 2010;Demmer et al, 2011a;Behnam Azad et al, 2016). Furthermore, small molecules have been labeled using an array of radiolabels with different tracers ( 18 F, 11 C, 64 Cu, 68 Ga, 89 Zr, or 177 Lu) either as substitutes of unlabeled atoms 748 Adlere et al at ASPET Journals on August 11, 2020 molpharm.aspetjournals.org Downloaded from or in a chelate complex.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, PET is a detection method used both in clinics and research and PET tracers are useful tools in theranostics (Yordanova et al, 2017). 89 Zr-labeled ACKR3-mAb (clone 11G8) was evaluated in vitro and in vivo by PET, which showed enhanced labeled-antibody uptake in high-ACKR3-expressing tumors, and serves as a viable diagnostic marker (Behnam Azad et al, 2016).…”
Section: Cxcr4 and Ackr3 Radioligandsmentioning
confidence: 99%
“…It was found that the expression of ACKR3 at protein and mRNA levels in precancerous breast cancer was much higher than that in adjacent and normal breast tissues 26 . Several studies have shown that the high expression of ACKR3 is positively correlated with the proliferation of breast cancer cells, indicating that ACKR3 has a positive effect on tumor growth 27‐29 . Furthermore, Boudot and his colleagues found that in estrogen receptor (ER) positive breast cancer, estradiol can promote the growth of ER positive breast cancer cells by producing a large number of CXCL12 and regulating CXCR4 and CXCR7 receptors of CXCL12, and the chemokine receptor CXCR4 can enhance the response of cells to estradiol 30 .…”
Section: The Role Of Chemokines/chemokine Receptors In Breast Cancermentioning
confidence: 99%